9B.05: ASSOCIATION OF PLASMA PARATHYROID HORMONE WITH NIGHTTIME BLOOD PRESSURE IN PRIMARY HYPERPARATHYROIDISM-THE "EPLERENONE IN PRIMARY HYPERPARATHYROIDISM" TRIAL. (June 2015) - Verheyen, N.; Wetzel, J.; Martensen, J.; Belyavskiy, E.; Schmidt, A.; Colantonio, C.; Catena, C.; Gaksch, M.; Grübler, M.R.; Kraigher-Krainer, E.; Pieske, B.; Meinitzer, A.; et al.
Abstract : Objective: High parathyroid hormone (PTH) is a cardiovascular risk factor. Elevated plasma PTH levels are independently linked with high nighttime blood pressure (BP) in hypertensive patients. We therefore investigated the association between PTH and nighttime BP in patients with primary hyperparathyroidism (pHPT). Design and method: We analyzed patients with pHPT who participated in the "Eplerenone in Primary Hyperparathyroidism" (EPATH) Trial. Blood sampling was performed after an overnight fast and all laboratory parameters were determined immediately after blood sampling. 24-hour ambulatory BP monitoring was performed using a certified device (Mobil-O-Graph, I.E.M., Stolberg, Germany). Patients with regular use of the PTH modifying drug cinacalcet or with a reduced left ventricular ejection fraction <= 45% were excluded. Results: We enrolled 120 patients (mean age: 66 +/- 10 years, 98 were females [82%]). Median PTH (IQR) was 94 pg/mL (79 – 113), mean systolic and diastolic nighttime BP were 117 +/- 17 mmHg and 68 +/- 10 mmHg, respectively. PTH was directly correlated with mean systolic and mean diastolic nighttime BP (Spearman rho = 0.246, p = 0.007; rho = 0.214, p = 0.019, respectively). In multivariate linear regression analyses adjusted for age, sex, cholesterol, HbA1c, intake of antihypertensive drugs, 25-hydroxy vitamin D and glomerular filtration rate (CKDEPI), PTH remained significantly related to mean systolic nighttime BP (adjusted beta-coefficient = 0.194, p = 0.047), while the relationship with mean diastolic nighttime BP was not significant (beta = 0.260, p = 0.109). Conclusions: Plasma PTH was associated with mean systolic nighttime BP in patients with pHPT, independently of potential confounders. These novel data from the EPATH Trial further support the notion that PTH directly interferes with nighttime BP regulation. Whether lowering circulating PTH concentrations reduces the burden of high BP remains to be shown in future studies.